Relationship between Periodontal Health and Adolescent Physical Performance Periodontal Health and Adolescent Physical Performance - Aulia Ramadhani; Aryo Dwipo Kusumo; Restu Nurhidayati; Nada Fajrina; Fathimah Hanan; Ayu Anggraini B; Faizal Khalis Ramadhani (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Oral health problems, including periodontal tissue problems, are important issues that need attention because they can affect a person’s quality of life and performance. The prevalence of the periodontal disease in all age groups in Indonesia is 96.58%. Purpose: This study aims to determine the effect of periodontal disease on adolescent physical performance. Method: This research was conducted in an analytic observational manner. The population of this research is adolescents aged 12-14 years in junior high schools in Surabaya, East Java, Indonesia as many as 101 students. Data collection used the Modified Gingival Index (MGI) method and the International Physical Activity Questionnaire (IPAQ). The data analysis used was the ETA correlation test. Result: In the distribution of dental health knowledge, most of the respondents had a low level of knowledge of 88.1%, low physical activity of 44.6%, and good gingival health based on the Modified Gingival Index of 52.5%. Conclusion: There is a significant difference in the level of respondents’ Modified Gingival Index based on the respondent’s experience of getting dental and oral care and the last time he received dental and oral care.